PENGARUH FAKTOR SOSIAL DAN EKONOMI PETANI TERHADAP PRODUKSI USAHA TANI SAWI DI INDONESIA - Mohammad Jon Tasrif; Gulda Patria (Fakultas Ekonomi Universitas Borobudur, 2022)
Abstract This research done to know the farmer’s economy social influence to the production of green mustard farm business and the contribution of green mustard farm business income to the total family income. The method of data analyze uses multiply regresion model, with “Ordinary Least Square” methode by SPSS application and Income equation. The results by test shows that all variables like age, education level, how long farm business, labour cost and sum of family depents, farm business size and modals influence real on green mustard farm business production. By partial test farm business size and modals influence real in positive ways on green mustard farm business but how long farm business influence in negative way on green mustard farm business production. Netto average income of farmer’s green mustard farm business is Rp 12.768.031,-/year (Income > UMR Cianjur City). The contribution of green mustard farm business income on total family income is 43,29%. Keywords: green mustard farm business, social economy, income